Hubungan Antara Self Concept dan Self Efficacy Terhadap Kesiapan Kerja Siswa Kelas XII di SMK Negeri 5 Kerinci - Esa Evioni; Bukhari Ahmad; Harmalis Harmalis (Indonesian Journal of Counseling and Development, 2022)
This study aims to determine the relationship between self-concept and self-efficacy in job readiness in class XII students at SMK Negeri 5 Kerinci. This research is a type of quantitative research with a correlational approach. The number of samples in this study was 59 students from class XII. The instruments used to collect data in this study were the scale of work readiness, self-efficacy, and self-concept. The data was processed using the Multiple Regression analysis methods with the help of a computer through the SPSS Version 21 application. The results showed that the correlation coefficient between self-concept and work readiness was 0.804 with a significant value of 0.000 <0.05, which means a positive relationship between self-concept and work readiness with a strong relationship level. Furthermore, the correlation coefficient between self-efficacy and work readiness is 0.846 with a significant value of 0.000 <0.05, which means a positive relationship exists between self-efficacy and work readiness with a strong level of connection. Then the value of the correlation coefficient (R) between self-concept and self-efficacy on readiness is 0.859 with a significance value of 0.000 <0.05. This shows a robust relationship between self-concept and self-efficacy in the work readiness of class XII students at SMK Negeri 5 Kerinci. The value of R^2 (R square) of 0.738 means that the percentage contribution between self-concept and self-efficacy to work readiness is 73.8%